2018
DOI: 10.1371/journal.pone.0199927
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat prevents hyperoxia-induced lung injury and pulmonary hypertension in neonatal rats without effects on long bone growth

Abstract: Bronchopulmonary dysplasia (BPD) remains the most common and serious chronic lung disease of premature infants. Severe BPD complicated with pulmonary hypertension (PH) increases the mortality of these infants. Riociguat is an allosteric soluble guanylate cyclase stimulator and is approved by the FDA for treating PH in adults. However, it has not been approved for use in neonates due to concern for adverse effects on long bone growth. To address this concern we investigated if administration of riociguat is ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
(104 reference statements)
1
8
0
Order By: Relevance
“…Newborn rats were randomized on postnatal day 1 (P1) into two groups to receive RA or hyperoxia, 85% O 2 as previously described 21 , 22 . On P14, pups were anesthetized, blood samples were collected by right ventricular puncture, and plasmas were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Newborn rats were randomized on postnatal day 1 (P1) into two groups to receive RA or hyperoxia, 85% O 2 as previously described 21 , 22 . On P14, pups were anesthetized, blood samples were collected by right ventricular puncture, and plasmas were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In literature review, we found that Riociguat possess anti‐inflammatory activity in various diseases (Toxvig et al, 2019). Riociguat was reported to contribute on anti‐inflammatory process via inhibiting the formation of NLRP‐1 inflammasome/IL‐1β cascade (Donda et al, 2018). When we compare these literatures and our current experiment, we observe consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers partially explained these findings by indication that NO needs oxygen for its formation and sildenafil only inhibits degradation of NO-induced cGMP, in contrast, riociguat directly stimulates guanylate cyclase and cGMP production [57] . Donda et al show that riociguat reduces inflammation and vascular remodelling, therefore protects lungs in rat model of hyperoxia-induced lung injury [58] . However, this study has similar construction as these regarding sildenafil and shows only effects of riociguat in prevention of lung injury, not in treatment of disease-changed lungs.…”
Section: Riociguatmentioning
confidence: 99%
“… Under hypoxic conditions riociguat was approximately 3-fold more potent than under physiological oxygen levels. Donda et al [58] Sprague-Dawley rats: Normoxia + placebo (6) Normoxia + riociguat (6) Hyperoxia + placebo (6) Hyperoxia + riociguat (6) Hemodynamical and histological analysis of rat pulmonary arteries. Riociguat significantly reduces inflammation and vascular remodelling in compare to placebo group, therefore it protects lungs in rat model of hyperoxia-induced lung injury.…”
Section: Introductionmentioning
confidence: 99%